Hábitos de higiene y el rendimiento escolar - Padilla Curay, Luz María (2017)
The theoretical framework was developed in which the subject of hygiene was analyzed as one of the key factors in the student's life, therefore in terms of academic performance, as healthy children will always be healthy, active and predisposed to develop any activity, researches know that hygiene is synonymous with cleanliness, asepsis, health welfare creating a culture of coexistence and improving interpersonal relationships among all human beings much more with those groups with which they are in a classroom of class, hygiene habits should proceed from home becoming a good practice applied within school. The research was used to is to know how the hygiene affects the children´s academic performance at Unidad Educativa Gral. Leónidas Plaza Gutierrez, based on the secondary objectives to reach the central objective and to be able to obtain the sufficient and relevant information that allows clear the situation. For which two surveys were applied one directed to the children of the institution and another to the teachers and an interview to the director to be able to have more reliable information of the problem at school and to know how their habits of Hygiene are both personal and at school. The methodology applied in the research was applied experimental documentary and field methods and the technique applied was the interview and the survey. The relevance of the research project is to determine the importance of hygiene and how it influences in children´s the educational performance of in children´s at Unidad Educativa Gral. Leonidas Plaza Gutiérrez, considering hygiene as the central axis for the integral development of students, facilitated through the development of hygiene standards to improve school performance, students will be active with physical and intellectual disposition to interact, be able to think, analyze, comment, reflect, thus demonstrating their quality in learning and therefore in their academic achievement. Based on the above, it was possible to develop the impact of this study both in the social and economic area of people who were taken to study and as a consequence of all that could be gathered in the investigation, several conclusions and recommendations were made, hoping being great value for the students of Unidad Educativa Gral. Leonidas Plaza Gutiérrez.